Dynamics of DNA-tracking by two sliding-clamp proteins. - Fu, T J (1996)
Bacteriophage T4 gene 45 protein (gp45) and Escherichia coli beta are DNA-tracking sliding-clamp proteins that increase processivity by tethering their conjugate DNA polymerases to DNA. gp45 also activates T4 late transcription. DNA loading of gp45 and beta requires ATP or dATP hydrolysis; efficient loading at primer-template junctions is assisted by single-stranded DNA-binding proteins. The kinetics of gp45 loading and tracking have been examined by DNase I footprinting of linear DNA with one blunt end, one primer-template junction, and binding sites for proteins that block gp45 tracking. DNA loading of gp45 can also be interrupted by adding the non-hydrolyzable ATP analog ATP-gamma-S. At saturation, DNA is very closely packed with gp45 or beta. When gp45 loading is interrupted, or when a segment of the track is blocked off, the gp45 footprint dissipates within seconds, but the DNA-tracking state of beta is much more stable. The stability of the tracking state of gp45 is, however, increased by the macromolecular crowding agent polyethylene glycol. We suggest that labile gp45 catenation directly generates the coupling of late transcription to DNA replication during bacteriophage T4 multiplication.